Association between nonalcoholic fatty liver and increased low‐level albuminuria in postmenopausal women in China: A cross‐sectional study - Su, Wanlu; Wang, Yuxia; Chen, Kang; Wang, Jie; Wang, Anping; Tang, Xulei; Yan, Li; Luo, Zuojie; Qin, Guijun; Chen, Lulu; Ning, Guang; Mu, Yiming (Journal of diabetes, 2021)
Background Several studies have suggested that nonalcoholic fatty liver disease (NAFLD) is associated with cardiovascular disease (CVD). The excretion of low‐level albuminuria (LLA) elevates as the prevalence of CVD increases. However, few studies have explored the association between NAFLD and LLA. Methods This cross‐sectional study included 31 147 Chinese adults (7664 men and 23 483 women). The “normal” level of albuminuria as determined by the urinary albumin to creatinine ratio (UACR) was below 30 mg/g. LLA was defined as a higher level within the “normal” albuminuria range (5.54 mg/g < LLA≤29.9 mg/g). The participants with NAFLD were defined as having a fatty liver index (FLI) ≥ 60. The FLI was calculated using the Bedogni equation. Results A positive association was found between UACR and FLI through multivariate linear regression analyses (nonstandardized β ± SE: .047 ± 0.004, P <.001). The logistic regression analyses revealed that NAFLD had adjusted odds ratios (ORs) showing a significant relationship with LLA in models 1 to 4 (all subjects: OR, 1.207; 95% CI, 1.098‐1.326; women: OR, 1.43; 95% CI, 1.26‐1.63; all P <.001); however, we did not find significant adjusted ORs among the men. In the stratified analyses, the relationship between NAFLD and LLA was significant among postmenopausal women with a body mass index ≥24 but <28 kg/m2, fasting plasma glucose ≥5.6 but <7.0 mmol/L, or postprandial plasma glucose ≥7.8 but <11.1 mmol/L and those aged below 60 years without moderate‐intensity exercise. Conclusions A noteworthy association between NAFLD and LLA was found among postmenopausal women who had borderline blood glucose values, were overweight, and did not engage in moderate‐intensity physical activity. 摘要 背景 有多项研究表明; 非酒精性脂肪肝(NAFLD)与心血管疾病(CVD)有关。低水平蛋白尿(LLA)的排泄随着CVD患病率的升高而增加。但是; 少有研究探索NAFLD和LLA之间的相关性。 方法 这项横断面研究包括31 147名中国成年人(7664名男性和23 483名女性)。由尿白蛋白与肌酐之比(UACR)确定白蛋白尿的“正常”水平为低于30 mg / g。 LLA被定义为“正常”蛋白尿范围内的较高水平(5.54 mg / g <LLA≤29.9mg / g)。NAFLD的定义为脂肪肝指数(FLI)≥60。FLI使用Bedogni方程计算。 结果 通过多变量线性回归分析; UACR与FLI之间存在正相关(非标准化β±SE:0.047±0.004; P <0.001)。逻辑回归分析显示; NAFLD比值比(OR)在调整混杂因素的模型1‐4中与LLA显着相关(所有受试者:OR; 1.207; 95%CI; 1.098‐1.326;女性:OR; 1.43; 95%CI; 1.26‐1.63；所有P <0.001)；然而; 在调整混杂因素后; 我们没有发现男性之间有显著的OR。在分层分析中; 在24≤体重指数<28 kg / m 2、5.6≤ 空腹血糖 <7.0 mmol / L或7.8≤餐后血糖<11.1 mmol / L以及60岁以下缺少中等强度运动的绝经后妇女中; NAFLD与LLA的相关性更为显著。 结论 在绝经后的妇女中; NAFLD和LLA之间存在显着的相关性; 且当这些妇女处于临界血糖值; 超重且缺少中等强度体育锻炼的状态下时; 两者的相关性更为明显。 Highlights The association between nonalcoholic fatty liver disease (NAFLD) and low‐level albuminuria was noteworthy in postmenopausal Chinese women. These results may be helpful for specific populations who are more likely to benefit from the detection and avoidance of increased risk of NAFLD.